Man of La Mancha [videorecording (DVD)] - Leigh, Mitch, 1928-2014; Rosenthal, Laurence, 1926- (MGM DVD., 2004)
Jailed during the Spanish Inquisition for offending the church, author Miguel de Cervantes is forced to act out one of his manuscripts for the entertainment of fellow inmates. Cervantes delivers a rapturous performance as the legendary Don Quixote, the chivalrous knight whose choice to see life as it should be, not as it is, takes him into battles with an imaginary foe and into romance with the beautiful Dulcinea.